Microbiome analyses of 12 psyllid species of the family Psyllidae identified various bacteria including Fukatsuia and Serratia symbiotica, known as secondary symbionts of aphids - Nakabachi, Atsushi; Inoue, Hiromitsu; Hirose, Yuu (BMC microbiology, 2022)
Psyllids (Hemiptera: Psylloidea) comprise a group of plant sap-sucking insects that includes important agricultural pests. They have close associations not only with plant pathogens, but also with various microbes, including obligate mutualists and facultative symbionts. Recent studies are revealing that interactions among such bacterial populations are important for psyllid biology and host plant pathology. In the present study, to obtain further insight into the ecological and evolutionary behaviors of bacteria in Psylloidea, we analyzed the microbiomes of 12 psyllid species belonging to the family Psyllidae (11 from Psyllinae and one from Macrocorsinae), using high-throughput amplicon sequencing of the 16S rRNA gene. The analysis showed that all 12 psyllids have the primary symbiont, Candidatus Carsonella ruddii (Gammaproteobacteria: Oceanospirillales), and at least one secondary symbiont. The majority of the secondary symbionts were gammaproteobacteria, especially those of the family Enterobacteriaceae (order: Enterobacteriales). Among them, symbionts belonging to "endosymbionts3", which is a genus-level monophyletic group assigned by the SILVA rRNA database, were the most prevalent and were found in 9 of 11 Psyllinae species. Ca. Fukatsuia symbiotica and Serratia symbiotica, which were recognized only as secondary symbionts of aphids, were also identified. In addition to other Enterobacteriaceae bacteria, including Arsenophonus, Sodalis, and "endosymbionts2", which is another genus-level clade, Pseudomonas (Pseudomonadales: Pseudomonadaceae) and Diplorickettsia (Diplorickettsiales: Diplorickettsiaceae) were identified. Regarding Alphaproteobacteria, the potential plant pathogen Ca. Liberibacter europaeus (Rhizobiales: Rhizobiaceae) was detected for the first time in Anomoneura mori (Psyllinae), a mulberry pest. Wolbachia (Rickettsiales: Anaplasmataceae) and Rickettsia (Rickettsiales: Rickettsiaceae), plausible host reproduction manipulators that are potential tools to control pest insects, were also detected. The present study identified various bacterial symbionts including previously unexpected lineages in psyllids, suggesting considerable interspecific transfer of arthropod symbionts. The findings provide deeper insights into the evolution of interactions among insects, bacteria, and plants, which may be exploited to facilitate the control of pest psyllids in the future.